Concerning Human Aspirations - Essays in Comparative Labor Law - Verge, Pierre (Relations Industrielles / Industrial Relations, 1986)
This article reviews the book, "Concerning Human Aspirations - Essays in Comparative Labor Law," by David Ziskind.